THE AUTHORITY OF PEOPLE’S CONSULTATIVE ASSEMBLY BY SUBSQUENT OF THE AMENDMENT OF THE 1945 CONSTITUTION OF THE REPUBLIC OF INDONESIA - Pebrihariati R, Sanidjar (Yustisia, 2017)
People’s Consultative Assemly (hereinafter reffered to MPR) membership consisting of members of the House of Representative (hereinafter reffered to DPR) and Regional Representative Council (hereinafter reffered to DPD) members indicates that the MPR is still viewed as a representative body of the people because of its membership elected in the general election. The change of position of the People's Consultative Assembly (MPR), then the understanding of the form of popular sovereignty is reflected in three branches of power, namely the representative institution, the President, and the holder of the judicial power. Problem formulation discussed are: 1) How is the position of the People's Consultative Assembly as the implementer of people's sovereignty in Indonesia before the amendment of the 1945 Constitution? 2) How the position of MPR members coming from the DPD after the Amendment of the 1945 Constitution of the Republic of Indonesia. The research method used in this research is Normative Law research method, which uses secondary data. The discussion in this research: 1) the MPR as the executor of the sovereignty of the People in Indonesia, prior to the 1945 amendment, we see in the provisions On Article 1 paragraph (2) of the 1945 Constitution stipulates that: "Sovereignty is in the hands of the people, and carried out according to the law basic". In the above article it contains three meanings, namely: a). The sovereignty of the people is implemented by all state institutions established in the Constitution, b). The sovereignty of the people must be subject to the constitution, c) constitutional supremacy. People's sovereignty is limited by the rules of the Constitution and constitutional democracy. 2) Position of MPR members originating from DPD after the Amendment of the 1945 Constitution of the Republic of Indonesia. After the fourth amendment of the 1945 Constitution, (hereinafter referred to as the 1945 Constitution of the Republic of Indonesia), there is a fairly fundamental change in both the state administration system and the state institutions in Indonesia .